A Multipurpose backtracking algorithm - Priestley, H; Ward, M (Elsevier, 1994)
A backtracking algorithm with element order selection is presented, and its efficiency discussed in relation both to standard examples and to examples concerning relation-preserving maps which the algorithm was derived to solve. © 1994 Academic Press. All rights reserved.